2020
DOI: 10.1016/j.iot.2020.100207
|View full text |Cite
|
Sign up to set email alerts
|

Internet of smart-cameras for traffic lights optimization in smart cities

Abstract: Smart and decentralized control systems have recently been proposed to handle the growing traffic congestion in urban cities. Proposed smart traffic light solutions based on Wireless Sensor Network and Vehicular Ad-hoc NETwork are either unreliable and inflexible or complex and costly. Furthermore, the handling of special vehicles such as emergency is still not viable, especially during busy hours. Inspired by the emergence of distributed smart cameras, we present a novel fuzzy logic approach to traffic contro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(11 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…ere are several research works on using cameras to count the number of vehicles for traffic management and optimization. A recent study using the Internet of smart-cameras is presented in [36]. e solution is based on WSN and VANET by deploying a very large number of cameras connected in a dedicated infrastructure.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…ere are several research works on using cameras to count the number of vehicles for traffic management and optimization. A recent study using the Internet of smart-cameras is presented in [36]. e solution is based on WSN and VANET by deploying a very large number of cameras connected in a dedicated infrastructure.…”
Section: Related Workmentioning
confidence: 99%
“…Although other studies already suggested the use of V2I communication as the basis of the traffic management system, in this paper, we provide a complete study and performance analysis for different traffic conditions. As stated before, this study does not require any extra hardware like counting cables, computer vision, and camera systems [21,36]. ere is no need for expensive and complex systems to extract useful features such as computer vision or deep learning approaches [5,39,40] or parallel processing [42].…”
Section: Related Workmentioning
confidence: 99%
“…Emergency cases inclusive algorithms explicitly discuss emergency cases. For example, Tchuitcheu et al [56] suggested a collision-free distributed algorithm for controlling traffic signals using the information provided by smart cameras. Their algorithm used smart cameras for real-time monitoring and assessment.…”
Section: B Emergency Cases Inclusive Algorithmsmentioning
confidence: 99%
“…In certain areas, traffic congestion in main roads has been a big issue with the shortage and restricted provision of public transport. If there is no initiative, this dilemma would be unmanageable [5,6].…”
Section: Introductionmentioning
confidence: 99%